2019
DOI: 10.1142/s1793431119500106
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility Analysis of Base-Isolated LNG Storage Tank for Selecting Optimum Friction Material of Friction Pendulum System

Abstract: The objective of this study is to establish a system for selecting the optimum friction material to meet the seismic performance requirements of a liquefied natural gas tank with a friction pendulum system (FPS). A methodology for determining the optimum frictional material using seismic fragility analysis is suggested, and it is applied to materials with various frictional coefficients for FPS. Seismic fragility curves with two different limit states are developed to determine the optimum friction material, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, more studies on the seismic performance of NPP structures are needed. Base isolators such as Lead Rubber Bearing (LRB) or friction pendulum systems can mitigate the possibility of damage to the civil structures and NPPs during an earthquake [1][2][3][4]. Numerous studies have been conducted on the effects of base isolators and the seismic performance of base-isolated NPP structures.…”
Section: Imentioning
confidence: 99%
“…Therefore, more studies on the seismic performance of NPP structures are needed. Base isolators such as Lead Rubber Bearing (LRB) or friction pendulum systems can mitigate the possibility of damage to the civil structures and NPPs during an earthquake [1][2][3][4]. Numerous studies have been conducted on the effects of base isolators and the seismic performance of base-isolated NPP structures.…”
Section: Imentioning
confidence: 99%
“…Waghmare et al [13] studied the shock absorption effect of the semi-active control strategy using liquid viscous damper on the liquid storage tank. Kim et al [14] established a set of optimal friction material selection system for friction pendulum isolation storage tank, and found that the lower friction coefficient is more helpful to prevent the damage of liquid storage tank by vulnerability analysis. Jiang et al [15] proposed the optimization design method of liquid storage tank with inertial container isolation system, found that the method met the requirements of sloshing wave height and effectively reduced the base shear force and isolation layer displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Nikoomanesh et al 16 proposed a vertical isolation system for liquid storage tanks, and the parameter research showed that the system was more effective for slender liquid storage tanks. Kim et al 17 established a set of optimal friction material selection system for friction pendulum isolation tank, and obtained a lower friction coefficient through vulnerability analysis, which was more helpful to prevent tank damage. Jiang et al 18 put forward the optimization design method of the tank with inertial vessel isolation system, and obtained that the method could meet the requirements of sloshing wave height and effectively reduce the base shear force and the displacement of isolation layer.…”
Section: Introductionmentioning
confidence: 99%